Changing dialysate composition to optimize acid‐base therapy. Issue 3 (3rd April 2019) - Sargent, John A.; Marano, Marco; Marano, Stefano; Gennari, F. John
Abstract: In response to rapid alkali delivery during hemodialysis, hydrogen ions (H + ) are mobilized from body buffers and from stimulation of organic acid production in amounts sufficient to convert most of the delivered bicarbonate to CO2 and water. Release of H + from nonbicarbonate buffers serves to back‐titrate them to a more alkaline state, readying them to buffer acids that accumulate in the interval between treatments. By contrast, stimulation of organic acid production only serves to remove added bicarbonate (HCO3 − ) from the body; the organic anions produced by this process are lost into the dialysate, irreversibly acidifying the patient as well as diverting metabolic activity from normal homeostasis. We have developed an analytic tool to quantify these acid‐base events, which has shown that almost two‐thirds of the H + mobilized during hemodialysis comes from organic acid production when bath bicarbonate concentration ([HCO3 − ]) is 32 mEq/L or higher. Using data from the hemodialysis patients we studied with our analytical model, we have simulated the effect of changing bath solute on estimated organic acid production. Our simulations demonstrate that reducing bath [HCO3 − ] should decrease organic acid production, a change we propose as beneficial to the patient. They also highlight the differential effects of variations in bath acetate concentration, as compared to [HCO3 − ], on the amount and rate of alkali delivery. Our results suggest that transferring HCO3 − delivery from direct influx to acetate influx and metabolism provides a more stable and predictable rate of HCO3 − addition to the patient receiving bicarbonate‐based hemodialysis. Our simulations provide the groundwork for the clinical studies needed to verify these conclusions.